2014
DOI: 10.1038/nm.3437
|View full text |Cite
|
Sign up to set email alerts
|

2-deoxy-2-[18F]fluoro-d-mannose positron emission tomography imaging in atherosclerosis

Abstract: Progressive inflammation in atherosclerotic plaques is associated with increasing risk of plaque rupture. Molecular imaging of activated macrophages with 2-deoxy-2-[(18)F]fluoro-D-glucose ([(18)F]FDG) has been proposed for identification of patients at higher risk for acute vascular events. Because mannose is an isomer of glucose that is taken up by macrophages through glucose transporters and because mannose receptors are expressed on a subset of the macrophage population in high-risk plaques, we applied (18)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
105
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(106 citation statements)
references
References 22 publications
1
105
0
Order By: Relevance
“…Several noninvasive modalities has been evaluated, but, unfortunately, a method that can properly assess all the aspects of plaque and based on non invasive approach either at imaging or biochemical level, is still unavailable [11]. We found that increased circulating levels of ADAM17 substrates were associated to a significant higher rate of second cardiovascular events in a cohort of patients with established vascular atherosclerosis.…”
Section: Discussionmentioning
confidence: 80%
“…Several noninvasive modalities has been evaluated, but, unfortunately, a method that can properly assess all the aspects of plaque and based on non invasive approach either at imaging or biochemical level, is still unavailable [11]. We found that increased circulating levels of ADAM17 substrates were associated to a significant higher rate of second cardiovascular events in a cohort of patients with established vascular atherosclerosis.…”
Section: Discussionmentioning
confidence: 80%
“…Several other PET tracers have been tested for use in atherosclerosis imaging, which might offer more specific markers of inflammation than 18 F-FDG or provide better methods for coronary artery imaging owing to inherently low myocardial tracer activity. These include 18 F-fluorodeoxymannose, the somatostatin receptor subtype-2 PET ligand 68 Ga-DOTATATE, 11 F-fluorocholine, and transient receptor protein receptor tracers, including 11 C-PK11195 [128][129][130][131]. Aside from inflammation, several other pathogenic mechanisms of atherosclerosis can be imaged using PET, including microcalcification, hypoxia, neo-angiogenesis, hematopoiesis, and HDL accumulation [126,[132][133][134][135].…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…FDM also restricted binding of anti-mannose receptor antibody to macrophages by approximately 35%, so mannose receptors may be an additional target for imaging of plaque inflammation [337]. A novel system for dual-modality imaging of atherosclerotic plaques using the glucose probes [ polymorphisms are implicated as a cause in diabetic nephropathy and GLUT1 expression levels are altered in various tissues under diabetic conditions.…”
Section: Atherosclerosismentioning
confidence: 99%